Optimization of Filter Algorithms in Bibliographic Databases to Improve the Retrieval of Scientific Information - Estupiñan Vera, Galo Enrique (Revista Minerva, 2024)
Efficiency in the search for scientific information is crucial for academic research. This study evaluates the performance of advanced filters on Scopus and Web of Science databases, using specific search equations. It analyzes how the implementation of operators and field codes affects the precision and relevance of the recovered documents. The role of Open Access filters and the use of English in the TITLE-ABS-KEY field codes is highlighted to obtain more precise results.
Keywords: research; filters; equation; results